Meta Analysis of the Effect of Applying the Problem Based Learning Model in Physics Learning to Improve Students' Ability to Solve Problems - Janna, Fadhillah; Ulfa, Aulia; Adinda, Ismi Gustia; Desnita, Desnita (Physics Learning and Education, 2024)
The meta-analysis method in this research was used to determine how problem-based learning activities influence problem-solving abilities. Analysis is carried out based on material units and levels/classes. Based on the results of the analysis, it was found that the mechanical material unit had an effect size of 0.83 in the high category, for the electric magnetic material unit it had an effect size value of 1.12 in the very high category, for the optical wave material unit it had an effect size of 1.66 with very high category, for thermodynamic material units it has an effect size of 1.41 in the very high category, and for fluid material units it has an effect size of 1.56 in the very high category. Then for class X it has an effect size of 1.19 in the very high category, for class XI it has an effect size of 1.35 in the very high category and for class In conclusion, for the optical wave material unit, it has an effect size of 1.81 which has a very high influence on students' ability to solve problems and for class XI level it has an effect size of 1.35 which has a very high influence on students' ability to solve problems.